Movements of the New Zealand school shark, Galeorhinus galeus , from tag returns - Rosemary J. Hurst; Neil W. Baglet; Graeme A. McGregor; Malcolm P. Francis (New Zealand Journal of Marine and Freshwater Research, 1999)
During the period March 1985 to January 1997, 3950 school sharks, Galeorhinus galeus (L), were tagged, mostly opportunistically during other research activities. Up to July 1997, 207 sharks had been recaptured. The best recovery rates were from sharks tagged with internal (8.8%) and dart (6.5%) tags and first caught by line methods (22%). The maximum distance travelled was 4940 km, the maximum time at liberty was 3505 days (9.6 years), and greatest average speed was 22.8 km/day. Most sharks (76%) moved less than 500 km, but the larger movements included 10% of sharks which had travelled over 1700 km to southern Australia. The proportion of sharks recaptured in their home Quota Management Areas (QMA) was 53% overall. However, the distance travelled increased significantly with time at liberty. After 2 years at liberty, only 22% of sharks were recaptured within a release QMA and 23% were recaptured in Australia. These findings suggest that future assessment of school shark fisheries within New Zealand waters should consider the species as one stock with a relatively high emigration rate to Australian waters.